Assessing the performance of educational research in Australian universities: an alternative perspective. Issue 2 (23rd February 2018) - Perry, Laura B.
ABSTRACT: This study uses bibliometric data to assess the performance of educational research in Australian universities. It provides an alternative perspective to the Australian government's Excellence in Research for Australia (ERA) assessment. ERA results suggest that the performance of educational research is substantially less compared to other disciplines, with only a handful of universities performing 'above world standard'. I use a range of indicators that capture citation impact and journal quality from Elsevier's SciVal research benchmarking tool to provide an alternative perspective that is authentic, transparent, comprehensive and multi-dimensional. The findings show that most Australian universities are performing above the world average in educational research. Australian universities perform especially well on the citation indicators, with more than 75% of universities performing above the world average on all three indicators. Performance on ERA is only moderately correlated with research performance in my analysis but is strongly related to one indicator, publication volume. This finding suggests that ERA assessments favour large entities and disadvantage smaller ones. The findings also suggest that the current ERA peer-review process may not accurately or fully reflect the performance of educational research in Australia. I anticipate that this alternative, bibliometric-based assessment will be a useful benchmarking tool for a range of purposes. I conclude with recommendations for future research.